A modern analytic method to solve singular and non-singular linear and non-linear differential equations - El-Ajou, Ahmad; Al-ghananeem, Haneen; Saadeh, Rania; Qazza, Ahmad; Oqielat, Moa’ath N. (Frontiers in Physics, 2023)
This article circumvents the Laplace transform to provide an analytical solution in a power series form for singular, nonsingular, linear, and nonlinear ordinary differential equations. It introduces a new analytical approach, the Laplace residual power series, which provides a powerful tool for obtaining accurate analytical and numerical solutions to these equations. It demonstrates the new approach's effectiveness, accuracy, and applicability in several ordinary differential equations problems. The proposed technique shows the possibility of finding exact solutions when a pattern to the series solution obtained exists; otherwise, only rough estimates can be given. To ensure the accuracy of the generated results, we use three types of errors, actual, relative, and residual error. We compare our results with exact solutions to the problems discussed. We conclude that the current method is simple, easy, and effective in solving nonlinear differential equations, considering that the obtained approximate series solutions are in closed form for the actual results. Finally, we would like to point out that both symbolic and numerical quantities are calculated using Mathematica software.